Anther smuts of Silene acaulis and S. uniflora in the Outer Hebrides, including an assessment of ITS genotypes of Microbotryum silenes-acaulis - Smith, Paul A. (IMA Fungus, 2017)
Anther smuts on Silene acaulis and S. uniflora from the Outer Hebrides, Scotland, UK), are analysed using morphological and molecular techniques, and found to represent Microbotryum silenes-acaulis and M. silenes-inflatae, respectively. This is the first identification of caryophyllaceous anther smuts in the Outer Hebrides according to modern species concepts and the first report of Microbotryum silenes-acaulis confirmed by molecular analysis from the British Isles. Additionally, the genetic structure of Microbotryum silenes-acaulis, based on all currently available ITS sequences, is analysed and discussed. Seven ITS genotypes are determined for Microbotryum silenes-acaulis, including three genotypes in North America and four genotypes in Europe. Compared to European accessions, all North American accessions share specific nucleotides and are genetically divergent.